HUBUNGAN MANUSIA DAN LINGKUNGAN DALAM CERPEN SUNDA KAWUNG RATU KARYA WAHYU WIBISANA KAJIAN EKOKRITIK - Taufik Rahayu (Badan Pengembangan dan Pembinaan Bahasa, 2020)
Humans and the natural environment should have a mutually beneficial and mutually beneficial symbiotic relationship. Humans need the natural environment to survive, as well as the natural environment requires humans to maintain their habitat. But in fact, humans actually take advantage of the natural environment and over-exploit it with greed, causing environmental damage. Humans tend to think of themselves as anthropocentric, which then backfires on themselves, because nature is corrupted and humans become miserable. In a Sundanese short story entitled